WEIGHT PRODUCT DALAM IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN BANTUAN BEDAH RUMAH - Dwi Marisa Efendi; Novita Novita (Jurnal informasi dan komputer, 2019)
North Lampung is a district in Lampung province. The government issued an aid program, he program is that every region is given the opportunity to manage aid funds, one of which is in the form of home surgery , This good government program is thirsty supported by the level of data accuracy, efficiency of the time of the recipient's management. Therefore in order to get good results. Then in this study using the weight product method in the implementation of decision support systems for home surgery recipients.